Paleoenvironmental conditions in the late Paleogene, Sumatra, Indonesia. (1st November 2015) - O'shea, Natalie; Arthur Bettis, E.; Zaim, Yahdi; Rizal, Yan; Aswan, Aswan; Gunnell, Gregg F.; Zonneveld, John-Paul; Ciochon, Russell L.
Highlights: First paleosol paleoenvironmental study of the Sumatran later Paleogene. Paleosol morphology shows the site is in the lower reaches of a large river system. Geochemical and isotopic analyses support a seasonal "equatorial" environment. Sedimentary structures and ichnofossil evidence indicate marine influence. Abstract: A stratified paleosol sequence exposed in an open pit mine in central Sumatra provides a record of the paleoenvironmental conditions in the lower reaches of a large river system in the late Paleogene (latest Eocene or Oligocene). Morphological, geochemical, and stable isotope data suggest that the sequence represents a mosaic of local environmental conditions changing from estuarine to riverine up section. Weakly expressed soils formed on low-lying estuary surfaces, while more well expressed soils formed on higher, better drained surfaces. Peatlands (coal) with clayey subsoils were along the estuary margins. Well-expressed soils with evidence of clay translocation and chemical weathering become more common higher in the section where alluvial deposits associated with a meandering river are dominant. Stable carbon isotope ratios support a paleolandscape dominated by C3 plants with input by C4 vegetation limited to a few intervals. Finally, whole-rock geochemistry suggests moderate chemical weathering consistent with a tropical locality. This multi-proxy paleoenvironmental reconstruction suggests a highly productive lowland forest environment at this locality in the late Paleogene and provides the first direct examination of the terrestrial environment in Sumatra at this time. The limited fossil record in Island Southeast Asia during this time period is likely a result of poor bone and shell preservation in tropical forest environments combined with a general lack of systematic prospecting. However, our continuing work in this area has produced a relatively diverse assemblage of fossil vertebrates, now including fishes, amphibians, turtles, crocodiles, and mammals, as well as a growing diversity of fossil plants.